Association Between Feritine Levels and Severity of COVID19 In RSUP Dr. M. Djamil Padang - Elsa Purnama Sari; Irvan Medison; Russilawati Russilawati (Jurnal Respirologi Indonesia, 2022)
Background: Ferritin is one of the inflammatory markers used as a predictor for severity of COVID-19. Early assessment of severity is expected to be a priority in disease management. This study aims to determine the association between ferritin levels and the severity of confirmed COVID-19 patients at RSUP dr. M. Djamil Padang. Methods: This study is a retrospective cohort study on confirmed COVID-19 patients from January to May 2021. Chi-square analysis was calculated to assess the association between ferritin levels and clinical grade, the severity of the chest X-ray and the level of need for oxygen therapy. To assess the risk opportunities for ferritin levels based on each dependent variable, an association analysis was performed by calculating the Odds Ratio..Results: Characteristics of the patients were mostly female (54.25%), aged more than 50 years (59,00%), clinical grade above category 4 (54,75%), required oxygen therapy (74,75%), the severity of chest X-ray was mild (75.50%), ferritin level < 500 ng/ml (52.75%) and had no comorbidities (51.25%). This study found that ferritin levels correlated with clinical grade, severity of chest X-ray, and level of need for oxygen therapy with HFNC and ventilator (p<0.001). Ferritin levels > 1000 ng/mL have a risk opportunity for clinical grade category 7 OR 8.28 (95% CI 2.69-25.41), severe chest X-ray severity OR 5.52 (95% CI 2.55- 11.97) and need for oxygen therapy with HFNC and ventilator, OR 4.76 (2.70-8.39) vs OR 7.69 (3.97-14.92)Conclusion: High ferritin levels significantly increase the risk of a severe clinical severity, severe chest X-ray and the level of need for oxygen therapy using HFNC and a ventilator in COVID-19 patients.Keywords: COVID-19, ferritin levels, severity